REARING OF RED TILAPIA (Oreochromis sp.) WITH DIFFERENT FILTER ON RECIRCULATION SYSTEM - Veronika Manurung; Mulyadi Mulyadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            This research was conducted for 45 days from of August until September 2017 in Pond and Hatchery Technical Attendence Unit Laboratory, Fisheries and Marine Faculty University of Riau. The purpose of the research was to determine the effect of water filter system that can improve water quality parameters in tilapia fish aquaculture. The research method was experiment with four treatments and three replications. Recirculation system using (Po) control, while the recirculation system (P1) using zeolite, where a weight of each filter material was 270 g (P2) using charcoal and P3 recirculation system using poor sand. Treatment of P1 gave the best results of water quality, temperature 26 – 30 ᵒC, pH 6.4 -8.2, DO 5.7 – 6.8 mg/L, amonia (NH3) 0.04 – 0.21 mg/L, nitrite (NO2) 0.03 – 0.35 mg/L, nitrate (NO3) 0.54 – 1.57 mg/L, the absolute growth rate of 4.86 g, then an absolute length  growth were 3.86 cm,  a daily growth rate  3.61 %, survival rate of 98.33 %, and the food efficiency of 75.25 %. Keywords : Resirculation system, water quality, Oreochromis